Assessment of BIM Implementation among MEP Firms in Nigeria - Chen Wang; Shittu Hammed Adetola; Hamzah Abdul-Rahman (Institute of Advanced Engineering and Science, 2015)
The purpose of this study is to assess the awareness level and potential challenges for Building Information Modelling (BIM) adoption among the Mechanical, Electrical and Plumbing (MEP) design consultants and contractors in Nigeria, and to get the perspective of BIM in the industry. The research method used in this study was a fieldwork survey using structured questionnaires. The results from the responses were analysed using descriptive statistics, one-way ANOVA test for statistical significant difference, Chi-Square test, and Cross Tab analysis. The findings from the survey show that Nigeria MEP firms have a relatively high level of awareness toward BIM technology. The Most important challenges identified as barriers for BIM adoption are lack of technical expertise on BIM tools utilisation, lack of awareness of BIM technology, and high investment cost in training staff, process change, and software/hardware upgrade.